Transmission electron microscopy of precipitation in fine-grained heat-affected zone of Grade91 steel weld during creep exposure. (April 2022) - Peansukmanee, Somporn; Phung-on, Isaratat; Poopat, Bovornchok; Pearce, John T.H.; Tsuda, Kenji; Nusen, Sankum; Chairuangsri, Torranin
Abstract: Precipitation during creep exposure at 550 °C in the fine grain heat-affected zone of a Grade91 steel weld produced by gas tungsten arc welding with no filler and post-weld heat treatment at 760 °C for 30 min. has been investigated. The applied tension load during creep testing was 165 MPa, the creep rupture time was 1138 hrs. (100% creep aging), and the creep exposure times were 911, 569, 341, 223 and 114 hrs. for 80%, 50%, 30%, 20% and 10% creep aging, respectively. Light microscopy and scanning electron microscopy were used to examine the heat-affected zone in the steel weld. Grain size in the fine grain heat-affected zone was measured by a circular intercept method on secondary electron images from scanning electron microscopy. Precipitates were detached from the fine grain heat-affected zone by a carbon-film extraction replica technique and investigated by transmission electron microscopy. During creep, a continual increase in grain size was observed in the fine grain heat-affected zone, starting from about 1.70 µm after post-weld heat treatment to about 2.30 µm at 100% creep aging. Precipitates found during creep were M23 C6, M7 C3, M6 C, MX, M2 X and high-Si Laves phase. M23 C6 was found in all creep conditions until rupture, mainly at prior austenite grain boundaries and sub-boundaries. M7 C3, M6 C and high-Si Laves phase were observed during creep aging, mainly nearby grain boundaries and sub-boundaries. Relatively fine MX and M2 X were found after 20% creep aging until rupture, mainly within grain interiors. Detailed criteria for identification of these precipitate phases, based mainly on energy dispersive X-ray spectrometry and selected area electron diffraction using transmission electron microscopy, is given and a major cause of premature loss of creep strength in Grade91 steel weld is discussed. This is important in understanding creep behavior of steel parts used for boiler tubing, heat exchangers, and steam piping systems in fossil-fuel power plants. Highlights: During creep, an increase in grain size was observed in FGHAZ of Grade 91 steel weld. Precipitates found in FGHAZ during creep were M23 C6, M7 C3, M6 C, MX, M2 X and high-Si Laves phase. Detailed criteria for identification of precipitate phases based mainly on TEM-EDS were given.